An anaerobic hybrid bioreactor for biologically enhanced primary treatment of domestic wastewater under low temperatures. Issue 11 (10th August 2018) - Pfluger, Andrew; Vanzin, Gary; Munakata-Marr, Junko; Figueroa, Linda
Abstract : Anaerobic hybrid reactor system for the generation of methane-rich biogas and energy. An energy-positive alternative to conventional primary treatment of raw domestic wastewater. Abstract : Anaerobic treatment of domestic wastewater is a methane-generating alternative to the current aerobic wastewater treatment paradigm. To explore biologically enhanced primary treatment of domestic wastewater, a pilot-scale hybrid reactor system, consisting of a three-compartment anaerobic baffled reactor (ABR) and an anaerobic fixed film reactor (AFFR), was operated for 720 days under low wastewater temperatures. The ABR-AFFR removed 49% of organics (as chemical oxygen demand, COD) and 72% of suspended solids, exceeding the performance of conventional primary treatment and achieving secondary discharge standards for suspended solids under warmer wastewater temperatures (>20 °C). The ABR-AFFR produced stoichiometric volumes of methane (0.36 L CH4 per g COD removed), at times exceeding the calculated theoretical maximum methane production from biodegradable organic removal. The mean electrical energy potential of gaseous CH4 produced by the ABR-AFFR was 0.16 kWh m −3 wastewater treated (assuming 32% electrical energy conversion efficiency). Examination of the microbial communities under warm (23 °C) and cold (12 °C) wastewater temperatures indicates that Euryarchaeota was in higher relative abundance under cold wastewater temperatures and that Methanosaeta, an acetate-utilizing methanogen, dominated the methanogenic community. The difference in community structure under varying wastewater temperatures indicates that long-term studies are required before accurate models tying system performance to community structure can be constructed. Results of this study suggest that the ABR-AFFR may be a viable methane-generating alternative to conventional primary treatment in an anaerobic-aerobic treatment paradigm.